Solid-phase radioimmunoassay for the detection of rotavirus. - Middleton, P J (1977)
A solid-phase radioimmunoassay method has been developed for the detection of rotavirus in the form of a purified antigen and in stool. The parameters of the radioimmunoassay were examined and optimized to give high sensitivity and same-day results. Compared with electron microscopy, the assay is up to 10 times as sensitive for detection of the virus in stool and up to 128 times as sensitive for detection of a purified virus antigen. In a field study on stool specimens it was at least as efficient as electron microscopy.